(3GdJMQjQ aj TQM GdLGeY GdcHjQs - (3LeGd GdOjf CHi GdeMGeO eMehO Hf CMeO GdHNGQj GdMUjQis; (3eMeO Hf GdMSf GdTjHGfjs ((3CHh GdYjfjf YWjI s)
(3ChdgG (B:s
(3jHOC HcJGH GdUdGI s
(3BNQgG (B:s
(3jfJgi HHGH ef GdCjeGf GdJi jbY ajgG GdJNjjQ hGdJi dGjbY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdMfajs